Meninjau tahap keupayaan jagaan diri untuk melakukan aktiviti hid up harlan dalam kalangan pesakit strok di Hospital Universiti Sains Malaysia (HUSM) - Muhammad Kamil, Che Hasan (PPSP, Universiti Sains Malaysia, 2007)
Stroke is the third cause of death in Malaysia. Those who has stroke attack undergo various of functional disable in order to make activity of daily living. Their level of functional is need to evaluate and study to provide various kinds of facility to optimize their ability without rely upon others. Objectives: To know level of functional among stroke patients in daily living activity after stroke attack, aspects of self-care related to activity of daily living. Methodology: 34 stroke patients which is admitted to Hospital Of University Science Malaysia that are rehabilitation phase (three days after being warded) are evaluated their functional of ability by using Functional Independence Measurement (FIM). Results: Percentage oflevel of functional motor shows 58.8% very dependent, 35.3% moderate dependent and 5.9% not dependent. Level of functional cognitive as many as 23.5% very dependent, 64.71% moderate dependent, and 11.76% not dependent. Conclusion: Level of independence of self-care among stroke patients overall is surrounded within highly dependent for motor function and moderately dependence for cognitive function. Healthcare provider should be improved in order to maximize the ability of sroke patients to do activity. Keywords: level of functional, self-care, activity of daily living, stroke patient